Frege’s Conceptions of Elucidation - Wim Vanrie (Journal for the History of Analytical Philosophy)
I argue that discussions of Frege’s conception of elucidation have suffered from a conflation of two distinct issues: elucidation of primitive scientific terms, and elucidation of the logical categories. The former seeks to bring us to grasp the Bedeutung of terms that stand at the beginning of the chain of definitions of a scientific system. The latter cannot be understood on the model of securing agreement in Bedeutung at all. I show how existing discussions of Fregean elucidation insufficiently take this difference into account. I adumbrate what I take to be a more accurate understanding of Fregean elucidation of the logical categories, starting from the observation that Frege, when engaged in such elucidation, consistently reverts to talking about signs. Frege, I argue, takes signs to possess logical features, and it is these logical features which his elucidations are meant to help us to grasp. For Frege, the nature of the logical categories lies in the signs. I argue that this reveals that Frege’s approach to elucidating the logical categories is incompatible with a realist framework according to which there is a logical order of reality that is prior to the logical order of language.